The Influence of Contextual Teaching and Learning (CTL) on the Learning Outcomes of the Subject of Aqidah Akhlak of Class VII Students at Muhammadiyah Grogol Middle School - Ahmad Aditya; Muhammad Kurniawan B.W; Ngatmin Abbas (Bulletin of Science Education, 2024)
The main problem of education today is that many students only understand the lessons of Aqidah Akhlak, but their application in everyday life is still lacking. The subjects of Aqidah Akhlak in schools are only viewed through cognitive aspects (knowledge) without looking at students in the real world so that learning Aqidah Akhlak is only limited to memorizing and taking notes. The purpose of this study is to analyze the effect of Contextual Teaching and Learning on student learning outcomes, so that it can provide a clear picture of the effectiveness of the learning. This study uses quantitative methods and quantitative approaches. The study was conducted at MTs Muhammadiyah Grogol with a sample of 31 students. Data collection was carried out using observation, documentation, and questionnaire methods. Data analysis used simple regression data analysis techniques by conducting normality tests and linearity tests, then a t-test was carried out to test the significance of the influence of independent variables on the dependent variable. The results showed that α = 0.05 and df = 29, the t-table value of the t distribution was 2.045. As the output of SPSS data processing t-count = 3.697 and t-table = 2.045. Because t-count (3.697) > t-table (2.045), then Ho is rejected and Ha is accepted. Sig. value. (p-value) in the SPSS output table is <0.001, which is much smaller than α = 0.05. Because p-value <α (0.001 <0.05) then Ho is rejected and Ha is accepted. This means that there is an influence of the application of Contextual Teaching And Learning (CTL) learning on the learning outcomes of the subject of aqidah akhlak class VII at MTs Muhammadiyah Grogol.